Surface Modification Processes for Use in LEO, GEO and Planetary Environments - Kleiman, Jacob I. (Mechanics and Advanced Technologies, 2019)
Abstract. ITL Inc. through its 30 years of activities in space exploration developed a number of unique processes for impairing new properties to space-bound materials that are exposed in LEO, GEO and planetary environments to space factors like atomic oxygen, ultraviolet radiation, charged energetic particles, etc. For materials flown in LEO missions, the atomic oxygen remains the major hazard. We developed a number of surface modification processes like Photosil, Implantox to change the surface structure of many polymer materials and paints and make them atomic oxygen resistive. For systems operating in GEO orbits the charging effects are among the major hazards. Two surface modification processed developed by ITL successfully solved these problems, while keeping the RF transparency of materials where necessary.